Indonesian Leadership Policies and Strategies In Facing The South China Sea Conflict - Aprianto Trianggoro Putro; Endro Legowo; Panji Suwarno; Pujo Widodo; Achmed Sukendro (CV. AFDIFAL MAJU BERKAH, 2023)
This research examines Indonesia's role in managing the South China Sea dispute using a conceptual framework of regional leadership that involves five models of leadership role impact. Indonesia's role in the South China Sea conflict is categorized as active but with limited impact. Despite Indonesia's active involvement in South China Sea conflict resolution efforts for over two decades, its impact has not reached the expected level. Indonesia has engaged in various cooperations and diplomacy that have successfully prevented open conflicts in the South China Sea region. Nevertheless, Indonesia's role in supporting internal solutions for the disputing parties remains limited due to several factors beyond Indonesia's control. These factors include the complexity of competition with China's power, low levels of trust among member states, a lack of technical cooperation in governing the South China Sea region, and the dilemmas of defense diplomacy with countries outside the region. This research highlights that Indonesia has the potential to act as a mediator and mediator in managing the South China Sea disputes, especially in non-traditional security issues such as Illegal, Unreported and Unregulated Fishing (IUU Fishing). Focusing on non-traditional security diplomacy may help minimize the impact of conflicts and enhance cooperation in the South China Sea region.